The influence of urban form on travel patterns. An application to the metropolitan area of Bordeaux - Guillaume Pouyanne (European Regional Science Association (ERSA), 2004)
The influence of urban form on travel patterns is of growing interest among researchers. It has been notably argued that high density, mixed land use settlements reduce automobile use and distances travelled, hence energy consumption per capita. A precise characterization of urban form calls analysis at an infra-urban level. We have questioned the interaction between land use and mobility in the metropolitan area of Bordeaux, France, by using OLS regressions for usual transportation variables and a multinomial logit model for modal shares. The results confirm a strong influence of both residential and firm density on mobility patterns. Mixed land use patterns doesn't seem to influence mobility. Some economic and demographic characteristics have an influence on travel patterns. Thus it is unavoidable to take them in account. But sometimes it leads to a logical indecision, and it is difficult to determine the direction of the causal relationship. Keywords : urban sprawl, density, compact city, land use – mobility interaction JEL classification : R12, R14, R41
Keywords: R12; R14; R41; 330; urban sprawl; density; compact city; land use – mobility interaction